L’impasse di Frege sulle funzioni predicative è condiviso da Aristotele e Wittgenstein? - Giouli, Virginia M. (Filosofia, 2023)
The idea of rejecting a certain form of transcendental realism fits perfectly with Wittgenstein’s and Aristotle’s anti-realistic account of the world, and may serve in a humanly accessible form of realism to implement the resolution of Frege’s epistemological impasses. Frege has taught us that it is possible to discover reality solely through the use of reason. Aristotle and Wittgenstein, on the other hand, have warned us that any such attempt at discovery is fraught with difficulty; it is the task of thinkers to painfully (even frustratingly) seek to uncover the order and laws underlying what really exists in the world. Frege’s rationality is finally seen to be decreasing, as it takes refuge in meanings of concepts and results in his almost total silence as regards their predicative functions. Able, if reluctant, to understand the way out of the impasse in that there can be no other criteria than the ordinary ones for what is habitually done, the way suggested by Aristotle’s use of the “square of oppositions”, Frege paves the way for a philosophical understanding of Aristotle’s and Wittgenstein’s rejection of a robust form of realism in favour of a less demanding form of it.